Tumour CD274 (PD-L1) expression and T cells in colorectal cancer. Issue 8 (5th May 2016) - Masugi, Yohei; Nishihara, Reiko; Yang, Juhong; Mima, Kosuke; da Silva, Annacarolina; Shi, Yan; Inamura, Kentaro; Cao, Yin; Song, Mingyang; Nowak, Jonathan A; Liao, Xiaoyun; Nosho, Katsuhiko; et al.
Abstract : Objective: Evidence suggests that CD274 (programmed death-ligand 1, B7-H1) immune checkpoint ligand repress antitumour immunity through its interaction with the PDCD1 (programmed cell death 1, PD-1) receptor of T lymphocytes in various tumours. We hypothesised that tumour CD274 expression levels might be inversely associated with T-cell densities in colorectal carcinoma tissue. Design: We evaluated tumour CD274 expression by immunohistochemistry in 823 rectal and colon cancer cases within the Nurses' Health Study and Health Professionals Follow-up Study. We conducted multivariable ordinal logistic regression analyses to examine the association of tumour CD274 expression with CD3 +, CD8 +, CD45RO (PTPRC) + or FOXP3 + cell density in tumour tissue, controlling for potential confounders including tumour status of microsatellite instability (MSI), CpG island methylator phenotype, long interspersed nucleotide element-1 methylation level and KRAS, BRAF and PIK3CA mutations. Results: CD274 expression in tumour cells or stromal cells (including immune cells) was detected in 731 (89%) or 44 (5%) cases, respectively. Tumour CD274 expression level correlated inversely with FOXP3 + cell density in colorectal cancer tissue (outcome) (ptrend =0.0002). For a unit increase in outcome quartile categories, multivariable OR in the highest (vs lowest) CD274 expression score was 0.22 (95% CI 0.10 to 0.47). Tumour CD274 expression was inversely associated with MSI-high status (p=0.001). CD274 expression was not significantly associated with CD3 +, CD8 + or CD45RO + cell density, pathological lymphocytic reactions or patient survival prognosis. Conclusions: Tumour CD274 expression is inversely associated with FOXP3 + cell density in colorectal cancer tissue, suggesting a possible influence of CD274-expressing carcinoma cells on regulatory T cells in the tumour microenvironment.